(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Due to the emergence of multimedia and Internet technologies, general educational schools of information technology have opened a wide path to education as an effective tool in the educational and communication processes. The role and influence of information technology in the development of a well-rounded personality, independent profession and professional self-preservation, professional skill development cannot be denied. Information in the educational process is found by the public and students using information technologies in the educational process. Children’s range of thinking expands, their knowledge increases. The role of independent work increases, it helps the child develop mentally, helps to heal the emotional-aesthetic circle, and to develop physical education. New technologies are created from the power of computer and information technologies, in education, training activities and in the development of creative thinking of students.